مدى استخدام مهارات التعلم النشط لدى معلمي المرحلة الأساسية الدنيا - بركات, زياد (جامعة الوادي - University of Eloued, 2018)
اهتمت هذه الدراسة بالتحقق من مدى استخدام معلمي المرحلة الأساسية الدنيا في المدارس الحكومية في محافظة طولكرم بفلسطين لمهارات التعلم النشط أثناء التدريس، لهذا الغرض طبقت استنبانة من إعداد الباحث مكونة من (39) فقرة على عينة مكونة من (232) معلماً ومعلمة، تم اختيار أفرادها بطريقة العشوائية الطبقية تبعاً إلى متغير الجنس. ولدى تحليل البيانات أظهرت نتائج الدراسة أن تقدير المعلمين الكلي لاستخدامهم التعلم النشط كان بمستوى مرتفع، كما أظهرت النتائج عدم وجود فروق جوهرية في مستوى تقديراتهم لاستخدام التعلم النشط تبعاً إلى متغيرات: الجنس، والخبرة، والتخصص، والمؤهل العلمي. وفي ضوء هذه النتائج اقترح الباحث عدة توصيات كان أهمها: عقد دورات تدريبيه للمعلمين، في كيفية توظيف إستراتيجية التعلم النشط، وإجراء دراسات تناول نفس الموضوع ولكن على فئة أخرى ومناطق مختلفة، وعقد ورش عمل وحلقات تنشيطية وشرح الإستراتيجيات التي تدعم التعلم النشط. مفتاحية. Abstract : Level of Use of Active Learning Skills for Lower Elementary Stage Teachers in the Public Schools at Tulkarm Governorate The study investigated the extent to which the teachers of the lower elementary stage in the public schools in Tulkarm governorate used the skills of active learning during teaching. For this purpose, a questionnaire was prepared by the researcher, consisting of (39) paragraphs on a sample of (232) teachers, In a randomized, methodical manner depending on sex and specialization. In the analysis of the data, the results of the study showed that the overall teachers' assessment of their active learning use was high, and the results showed no significant differences in their estimation of active learning according to gender, experience, specialization, and scientific qualification. In the light of these results, the researcher suggested several recommendations, the most important of which were: holding training courses for teachers, how to employ an active learning strategy, conducting studies on the same subject, but on another category and different areas; holding workshops and workshops.
مقال
Keywords: التعلم النشط.المهارات.الطلاب.المعلمين.المرحلة الاساسية